2018
DOI: 10.19184/nlj.v3i2.8580
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Fatigue and Sleep Quality among Patients with Heart Failure

Abstract: Heart failure (HF) patients may experience fatigue and poor sleep quality due to impairment in cardiac structure or function. These distressing symptoms may create a vicious circle leading to poor outcomes but often undervalued and ignored among patients. This study aimed to investigate the relationship between fatigue and sleep quality among patients with HF in Indonesia. A cross-sectional, correlational study design was performed with 153 convenience samples recruited from a cardiology outpatient department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(69 reference statements)
0
6
0
3
Order By: Relevance
“…Jika partisipan memilih tidak merasa kelelahan pada pertanyaan nomor 1, maka harus diberikan skor 0 semua pertanyaan yang tersisa (2-16). Kuesioner ini sudah digunakan pada populasi di Indonesia seperti pada pasien hemodialisis (Khusniyati, Yona, & Kariasa, 2019) dan gagal jantung (Lainsamputty & Chen, 2018). Skor uji reliabilitas konsistensi interlah kuesioner MAF dalam penelitian ini adalah 0,95.…”
Section: Materials Dan Metodeunclassified
“…Jika partisipan memilih tidak merasa kelelahan pada pertanyaan nomor 1, maka harus diberikan skor 0 semua pertanyaan yang tersisa (2-16). Kuesioner ini sudah digunakan pada populasi di Indonesia seperti pada pasien hemodialisis (Khusniyati, Yona, & Kariasa, 2019) dan gagal jantung (Lainsamputty & Chen, 2018). Skor uji reliabilitas konsistensi interlah kuesioner MAF dalam penelitian ini adalah 0,95.…”
Section: Materials Dan Metodeunclassified
“…Psychometric analysis of the PSQI revealed good reliability (internal consistency) in hypertensive population, ranging from 0.76-0.80 (Hsu, Chen, Ho, & Lin, 2018;Kara & Tenekeci, 2017). Bahasa Indonesian version of PSQI has been used previously, with a Cronbach's alpha of 0.76 in heart failure patients (Lainsamputty & Chen, 2018).…”
Section: Demographicmentioning
confidence: 99%
“…A recent systematic review on depression on patients with HF found a global depression prevalence of 28.1% for moderate to severe symptoms, with a range from 11.3-50.0% [4]. Emerging evidence underscores poor sleep quality, fatigue, and social isolation as signi cant correlates of depressive symptoms in patients with HF [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to HF-related symptoms such as nocturnal dyspnea and palpitation, most of patients with HF reported poor sleep quality, with a proportion ranging from 70-90% [5,6]. Poor sleep quality usually has negative impacts on patients' health and well-being, in terms of physical, social, and mental aspects [6].…”
Section: Introductionmentioning
confidence: 99%